A new species of Anthostomella on Magnolia liliifera from northern Thailand - Promputtha I. (2014)
Anthostomella monthadoia sp. nov. collected from dead leaves of Magnolia liliifera in northern Thailand is described and illustrated with interference light micrographs. The new species is compared with similar taxa and a key to species of Anthostomella from Thailand is provided.